Genetic association of growth traits with carcass and meat traits in Nellore cattle - Tonussi, R. L.; Espigolan, R.; Gordo, D. G. M.; Magalhaes, A. F. B.; Venturini, G. C.; Baldi, F.; Oliveira, H. N. de; Chardulo, L. A. L. [UNESP]; Tonhati, H.; Albuquerque, L. G. de (Funpec-editora, 2015)
The aim of this study was to estimate genetic and phenotypic associations of growth traits with carcass and meat traits in Nellore cattle. Data from male and female animals were used for weaning weight (WW; N = 241,416), yearling weight (YW, N = 126,596), weight gain from weaning to yearling (GWY, N = 78,687), and yearling hip height (YHH, N = 90,720), respectively; 877 male animals were used for hot carcass weight (HCW) and 884 for longissimus muscle area (LMA), backfat thickness (BT), marbling score (MS), and shear force (SF). The variance components were estimated by the restricted maximum likelihood method using three-trait animal models that included WW. The model for WW included direct and maternal additive genetic, maternal permanent environmental, and residual effects as random effects; contemporary group as fixed effects; and age of dam at calving and age of animal as covariates (linear and quadratic effects). For the other traits, maternal effects and the effect of age of dam at calving were excluded from the model. Heritability ranged from 0.10 +/- 0.12 (LMA) to 0.44 +/- 0.007 (YW). Genetic correlations ranged from -0.40 +/- 0.38 (WW x LMA) to 0.55 +/- 0.10 (HCW x YW). Growth, carcass, and meat traits have sufficient genetic variability to be included as selection criteria in animal breeding programs.
Keywords: Genetic correlation; Longissimus muscle area; Shear force; Zebu